(untitled) (Global Journal of Medical Research, 2020)
Assuming home care for the elderly, we aimed to create a nursing food that can be created even at home, considering the combination of thickeners and foods, and creating useful data. Therefore, we used two types of thickeners that can purchase at pharmacies and three types of commercially available nursing food that can eat without chewing. Line Spread Test Start Kit (LST) manufactured by SARAYA used for viscosity measurement. The two types of thickeners used this time became more viscous when added to the food. And the viscosity of the food could be maintained over time (this time after 5minutes). However, in the case of foods rich in lipids, the thickener B was able to maintain the viscosity more than the thickener A. It is necessary to select a thickener that is compatible with the raw material ratio of the food.